Dynamics of Soil Bacterial and Fungal Communities During the Secondary Succession Following Swidden Agriculture IN Lowland Forests - Lin, Qiang; Baldrian, Petr; Li, Lingjuan; Novotny, Vojtech; Heděnec, Petr; Kukla, Jaroslav; Umari, Ruma; Meszárošová, Lenka; Frouz, Jan (Frontiers in Microbiology, 2021)
Elucidating drivers of soil microbial communities after disturbance is crucial for understanding ecosystem dynamics and sustainability. However, despite the widespread practice of swidden agriculture in tropical forests, knowledge about microbial community succession in this system is limited. Here, amplicon sequencing was used to investigate effects of soil ages (2, 5-10, 20-40 and ≥60 years) after disturbance, geographic distance (from 0.1 km to 10 km) and edaphic property gradients (soil pH, conductivity, C, N, P, Ca, Mg and K), on soil bacterial and fungal communities along a chronosequence of sites representing the spontaneous succession following swidden agriculture in lowland forests in Papua New Guinea. During succession, bacterial communities (OTU level) as well as its abundant (OTU with relative abundance > 0.5%) and rare (< 0.05%) subcommunities, showed less variation but more stage-dependent patterns than those of fungi. Fungal community dynamics were significantly associated only with geographic distance, whereas bacterial community dynamics were significantly associated with edaphic factors and geographic distance. During succession, more OTUs were consistently abundant (n=12) or rare (n=653) for bacteria than fungi (abundant=6, rare=5), indicating bacteria were more tolerant than fungi to environmental gradients. Rare taxa showed higher successional dynamics than abundant taxa, and rare bacteria (mainly from Actinobacteria, Proteobacteria, Acidobacteria and Verrucomicrobia) largely accounted for bacterial community development and niche differentiation during succession. Large effect of geographic distance on fungal community especially on symbiotic and pathogenic fungi supports Janzen-Connell hypothesis about substantial rule of spatial variation in fungal communities in maintaining tree diversity in rain forests.